The Influence of Leader Skills, Madrasah Environmental Situation and Leader Behavior on Madrasah Effectiveness in Jambi Province - Irama Silalahi, Dedi; Umar, M. Hasbi; Risnita (Darul Ilmi Bina Insan Foundation, 2023)
This research investigates the impact of leader skills, madrasah environmental conditions, and leader behavior on the effectiveness of madrasahs in Jambi Province, both individually and collectively. Utilizing a quantitative approach with a survey method, the study focuses on teaching staff across madrasahs in the region. The research includes a population of 128 individuals, with total sampling used to select participants. The study hypothesizes that leadership skills, the madrasah environment, and leader behavior significantly influence madrasah effectiveness, both independently and together. Path analysis is employed to test this hypothesis. The findings reveal that leadership skills (X1), the madrasah environment (X2), and leadership behavior (X3) collectively account for 97.1% of the variance in madrasah effectiveness (X4), with the remaining 2.9% attributable to other factors.